Lemmus lemmus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lemmus lemmus (Linnaeus 1758) [Mus] lemmus Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 59. Type Locality: Sweden, Lappmark. Vernacular Names: Norway Lemming. Synonyms: Lemmus borealis Nilsson 1829; Lemmus iterator (Gistel 1850); Lemmus norvegicus Desmarest 1822. Distribution: Mountains of Scandinavia and tundra from W Norway and Sweden to Kola (Kolskiy) Peninsula at W margin of the White Sea (NW Russia). Conservation: IUCN – Lower Risk (lc). Discussion: European populations reviewed by Tast (1982 a ) and Mitchell-Jones et al. (1999); Russia segment reviewed by Gromov and Erbajeva (1995). Phylogenetic analysis of cytochrome b haplotypes has revealed appreciable nucleotide divergence between Scandinavian and Siberian samples (Fedorov et al., 1999 b ); that genetic characterization, in combination with unique pelage coloration, supports the specific integrity of L. lemmus relative to the geographically allopatric L. sibiricus . Although now absent from the British Isles, the species occurred there during the Pleistocene and Late Glacial (Late Palaeolithic) times (Sutcliffe and Kowalski, 1976; Yalden, 1999). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 986, DOI: 10.5281/zenodo.7316535